Successful Literature in 21st Century Italy (Altre Modernità, 2025)
Successful Literature in 21st Century Italy(edited by) Luca Gallarini (Università degli Studi di Milano), Elisa Gambaro (Università degli Studi di Milano), and Mauro Novelli (Università degli Studi di Milano)